Melia dubia : An ideal tree for commercial agroforestry - Kumar, Sushil; Yadav, Ashok; Arunachalam, Ayyandar (Indian Farming, 2022)
Agroforestry or trees outside forests are vital for ensuring environmental resilience in terrestrial landscapes. In this regard, growing trees on farmlands i.e. agroforestry ensures livelihood security to the farming communities. Nonetheless, there are a few bottlenecks in the farmers’ adoption process of agroforestry trees as they ought to be fast-growing, deciduous straight bole, high market value, assured buyback, and low maintenance cost, etc. On these counts, and based on tree ideotypes for agroforestry, Melia dubia has both structural and functional traits for agroforestry, and essentially has market value as well. This study thus demonstrates various benefits of Melia dubia due to which it is gaining interest among the farmers and emerging as a sustainable and promising raw material for commercial agroforestry.